ENHANCING MUSTAHIK WELFARE THROUGH ISLAMIC SOCIAL FINANCE: AN INSTITUTIONAL PERSPECTIVE - Muhammad Rusdi; Mahmud Alfan Jamil; Sinsin Asmy (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
This research aims to determine the efforts of Islamic social financing institutions in Palembang, including Baznas and LAZ, to improve the welfare of mustahiq. The key informants in this research are the leaders of Baznas and LAZ. Data analysis techniques using qualitative descriptive. Research findings show that several strategies used by Baznas in distributing zakat, infaq and alms funds to improve mustahik welfare include, meeting basic needs, economic empowerment through productive zakat, educational program scholarships, free health services, priority distribution in remote and underdeveloped areas, cooperation and partnerships with the government, Ramadan programs and community empowerment. Conclusions to improve the welfare of mustahik Baznas and LAZ provide support to Mustahiq in the form of programs and strategies in collaboration with the government